Digital Transformation Assistance for Cooperative Financial Reports to Increase Transparency and Accountability : Pendampingan Transformasi Digital Laporan Keuangan Koperasi untuk Meningkatkan Transparansi dan Akuntabilitas - Latifah Asbaruna Binti Asbaruna; Ridwan Ismail Gorib; Armansyah M. Sarusu; Jajang Suherman; Selly Dwi Ambarwati (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
Village cooperatives often face limitations in transparent and digitized financial management, which affects accountability and decision-making quality. This activity aims to enhance transparency and accountability through digital transformation assistance in financial reporting at a village cooperative in Majalaya, Bandung Regency. A participatory approach was applied, including needs assessment, financial literacy training, implementation of a spreadsheet-based digital bookkeeping system, and mentoring with pre- and post-test evaluation. The results indicate a 24% increase in financial literacy among board members and 85% compliance in transaction recording using the digital system. In addition, periodic financial reports were prepared more systematically, supported by the implementation of financial Standard Operating Procedures (SOPs). This activity contributes to improved information transparency, internal control, and member trust in cooperative governance.